Triple jump for the optimal management of psoriatic arthritis: diet, sleep and exercise – a review - Ennio Lubrano; Kurt de Vlam; Rik Lories; Silvia Scriffignano; Fabio Massimo Perrotta; Mario Ronga (RMD Open)
Psoriatic arthritis (PsA) is a complex, multiform and chronic inflammatory disease characterised by the association of arthritis and psoriasis combined with other related conditions and comorbidities. Treatment of PsA has rapidly evolved by the introduction of new biological drugs and small molecules which allow to achieve disease remission or low disease activity in most of the patients. However, unmet treatment needs still persist for those patients with persistent disease activity or symptoms, impaired function, reduced quality of life or comorbidities. In this context, non-pharmacological approaches, including diet modifications, an adequate sleep quality and physical activity could provide additional benefits. In recent years, diet modifications, improvement of sleep quality and physical activity became an area of interest for researchers and some studies showed how a holistic non-pharmacological approach may ameliorate the quality of life of patients with PsA.The aim of this manuscript was to review the current evidence on the intriguing link and potential effects of diet, sleep and exercise in PsA patients. In particular, we reviewed the literature focusing on the possible benefits of a holistic approach to PsA patients considering lifestyle modifications.